Prevalence of bullying and violence among adolescents in Arab Gulf countries: a systematic review - Amani N. Alansari (19743643) (2025)
Aim This systematic review examined the prevalence, characteristics, risk factors, and consequences of bullying and violence among adolescents in Arab Gulf countries (AGC). Subject and methods We conducted a comprehensive search across PubMed, EMBASE, Scopus, and Web of Science databases from inception to April 2025. The quality of the included studies was assessed using the Newcastle–Ottawa Scale. Results A total of 16 cross-sectional studies from six Gulf countries were included. Findings revealed substantial bullying prevalence ranging from 12.6% to 83.28%, with verbal bullying (up to 89.4%) emerging as the predominant form, followed by physical (10.6-17.0%) and social bullying (approximately 6.0%). Educational settings constituted primary contexts for incidents, with specific high-risk locations identified, including corridors (54.8%), restrooms (17.5%), and classrooms (up to 80% in private schools). Gender-specific patterns were observed, with some studies reporting higher physical aggression among boys and others documenting increased psychological abuse and cyberbullying among girls. Mental health consequences were consistently significant, with bullied students demonstrating substantially increased risks of depression (OR 2.66) and anxiety (OR 2.89). Academic impacts included increased absenteeism (24–29%) and decreased performance. Conclusion This review highlights the widespread prevalence and serious consequences of bullying among adolescents in AGC, with clear gender differences and significant impacts on mental health and academic performance. The findings underscore the urgent need for tailored assessment approaches, gender-responsive interventions, integrated school-based mental health services, and culturally focused prevention strategies that address both traditional and cyberbullying in the rapidly evolving sociocultural context of the AGC. Other Information Published in: Journal of Public Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10389-025-02576-0